A survey on the parental attitudes toward the educational upliftment of their children and child-rearing styles in Barangay Canipaan, Hinunangan, Southern Leyte - Bastes, Rosanna Sumayo (Rosanna Sumayo Bastes, 1999)
With parents putting a high premium on the education of their children, relentless campaign was launched for giving the quality of existence and conditions antecedent for them to become progressive, peaceful and dynamic participants in the process of nation-building.